2021
DOI: 10.3390/cells10113169
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Gliomas in Machine Learning

Abstract: In the field of gliomas research, the broad availability of genetic and image information originated by computer technologies and the booming of biomedical publications has led to the advent of the big-data era. Machine learning methods were applied as possible approaches to speed up the data mining processes. In this article, we reviewed the present situation and future orientations of machine learning application in gliomas within the context of workflows to integrate analysis for precision cancer care. Publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…After fivefold cross validation, the average accuracy reached 85.4% (± 2.75, n = 5), suggesting no overfitting problem. In fact, most people think that SVM classifiers with rbf as its kernel function have difficulty producing the overfitting problem 38 .…”
Section: Resultsmentioning
confidence: 99%
“…After fivefold cross validation, the average accuracy reached 85.4% (± 2.75, n = 5), suggesting no overfitting problem. In fact, most people think that SVM classifiers with rbf as its kernel function have difficulty producing the overfitting problem 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, based on the evaluation of PROBAST in the results, the unclear source of data, inadequate sample size, inappropriate analysis methods, and lack of rigorous external validation are found to be the most frequent and critical risk factors in AI-aided renal ultrasound studies. As known, overfitting is a common problem in studies with a small number of samples, which is caused by not only the small size of the dataset but also the small number of patients ( 58 ). However, in the period covered by the search, the number of patients was not mentioned in nearly a quarter of AI-aided renal ultrasound studies.…”
Section: Discussionmentioning
confidence: 99%
“…In order to separate curcuminoids, thin-layer chromatography (TLC) was utilized, and the Rf values for curcuminoids from C, DMC, and BDMC were, respectively, 0.75, 0.55, and 0.27 for curcuminoids from C, DMC, and BDMC [ 36 ]. With the enhanced resolution of the Rf value, it was established that chloroform and methanol could be utilized as solvents in column chromatography for the separation and separation of diverse compounds [ 37 ]. When Gupta et al explored alternative compositions of the mobile phase for the separation of curcuminoids, it was revealed that utilizing chloroform and methanol (95 : 5) as the mobile phase allowed them to accomplish the necessary separation.…”
Section: Methodsmentioning
confidence: 99%